Noradrenaline content of the hypothalamus and brain-stem of rats inoculated with Trypanosoma Cruzi - Cosenza, Ramon M.; Machado, Conceição R. S.; Machado, Angelo B. M. (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
Noradrenaline was assayed fluorimetrically in the hypothalamus and brainstem of rats killed 20 and 32 days after inoculation with the Y strain of T. cruzi (300,000 trypomastigotes i.p.). In these animals and their normal controls the right atrial appendages were submitted to the glyoxilic acid fluorescence technique for the demonstration of noradrenergic nerves. The noradrenaline content of the brain-stem and hypothalamus of the infected animals was not significantly different from that of controls. In the atrial appendages, however, an almost complete noradrenergic denervation was observed. This result indicates that the mechanism involved in neuronal lesion in Chagas'disease discriminates between peripheral and central noradrenergic neurons.